2010
DOI: 10.2146/ajhp090344
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia due toShewanella putrefaciens

Abstract: A 39-year-old man developed ventilator-associated pneumonia evidently caused by S. putrefaciens. The pneumonia resolved after treatment with cefepime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Shewanella species are marine bacteria but have been reported as rare human pathogens (Holt et al, 2005). The most common Shewanella species associated with human infections are S. algae and S. putrefaciens (Holt et al, 2005), both of which have been identified as the cause of a variety of infections such as bacteraemia, pneumonia, meningitis and soft tissue infection (Brink et al, 1995;Jorens et al, 2004;Pagani et al, 2003;Tucker et al, 2010;Yilmaz et al, 2007). However, the species identification of previous reports was generally performed using biochemical reactions or commercially supplied automated microbiology systems.…”
Section: Case Reportmentioning
confidence: 99%
“…Shewanella species are marine bacteria but have been reported as rare human pathogens (Holt et al, 2005). The most common Shewanella species associated with human infections are S. algae and S. putrefaciens (Holt et al, 2005), both of which have been identified as the cause of a variety of infections such as bacteraemia, pneumonia, meningitis and soft tissue infection (Brink et al, 1995;Jorens et al, 2004;Pagani et al, 2003;Tucker et al, 2010;Yilmaz et al, 2007). However, the species identification of previous reports was generally performed using biochemical reactions or commercially supplied automated microbiology systems.…”
Section: Case Reportmentioning
confidence: 99%
“…In recent years, Shewanella has also been reported to be associated with food poisoning [13]. Diseases associated with the respiratory tract are rare and Shewanella strains have been recovered from sputum of a patient with chronic obstructive airway disease [14], a lung aspirate of a patient with lung tumor [15] and BALF specimens of two patients with ventilator-associated pneumonia [16, 17]. In additional, Shewanella have also been thought to play important roles in other cases of empyema or pneumonia [14, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Shewanella putrefaciens is a Gram-negative, non-fermentative, oxidasepositive, motile bacillus, conditional pathogen. In recent years, some clinical infections caused by Shewanella putrefaciens were reported, [2][3][4][5] and the bacteria can be isolated from the patients' blood, pus, urine, sputum and wound secretions. This is the first time in our hospital that Shewanella putrefaciens in the cerebrospinal fluid specimen was detected.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some clinical infections caused by it were reported. There were a variety of clinical syndromes including bacteremia, skin and soft tissue infections, pneumonia [2,3], etc. Hence, corresponding research is generally focused on opportunistic infection and has reached a basic consensus.…”
Section: Introductionmentioning
confidence: 99%